2009
DOI: 10.1016/j.vaccine.2009.03.082
|View full text |Cite
|
Sign up to set email alerts
|

A live attenuated H7N3 influenza virus vaccine is well tolerated and immunogenic in a Phase I trial in healthy adults

Abstract: Background-Live attenuated influenza vaccines (LAIV) are being developed and tested against a variety of influenza viruses with pandemic potential. We describe the results of an open label Phase I trial of a live attenuated H7N3 virus vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
96
3
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 60 publications
4
96
3
4
Order By: Relevance
“…Activated B cells called antibody secreting cell (ASC) produce antibodies and detailed analysis of these cells may shed more light on humoral correlates of protection. H7-specific ASC responses are elicited after H7 vaccination [3,21], and the level of response was similar to that observed in immunologically naïve children after inactivated seasonal vaccination [22], suggesting that these vaccines do not effectively activate B cells. The goal of vaccination is to elicit effective memory B cells (MBC), which can rapidly differentiate into plasmablasts secreting high affinity-specific IgG antibodies to rapidly neutralize the virus.…”
supporting
confidence: 51%
“…Activated B cells called antibody secreting cell (ASC) produce antibodies and detailed analysis of these cells may shed more light on humoral correlates of protection. H7-specific ASC responses are elicited after H7 vaccination [3,21], and the level of response was similar to that observed in immunologically naïve children after inactivated seasonal vaccination [22], suggesting that these vaccines do not effectively activate B cells. The goal of vaccination is to elicit effective memory B cells (MBC), which can rapidly differentiate into plasmablasts secreting high affinity-specific IgG antibodies to rapidly neutralize the virus.…”
supporting
confidence: 51%
“…Our laboratories have previously generated live attenuated H1N1, H2N2, H5N1, H6N1, H7N3, H7N7, H7N9, and H9N2 viruses and found that these candidate vaccines were safe and efficacious in conferring protection against wild-type (wt) viruses in mice and ferrets (31)(32)(33)(34)(35)(36); several of these vaccines have been evaluated in phase 1 clinical trials (33,37,38).…”
mentioning
confidence: 99%
“…Thus far, we have generated and evaluated vaccines against seven different influenza virus subtypes in preclinical studies and phase I clinical trials in healthy adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Although they replicated and were immunogenic and efficacious in mice and ferrets, the pandemic LAIV (pLAIV) viruses did not replicate efficiently in seronegative healthy adults (18)(19)(20)(21)(22), although some of the pLAIV viruses (e.g., H9N2 and H7N3) induced a robust immune response in vaccinees (21,22).…”
mentioning
confidence: 99%